Selected Topics on Improved Oil Recovery Transactions of the International Conference on Improved Oil Recovery, 2017 (Springer Singapore, 2018)
This book presents articles from the International Conference on Improved Oil Recovery, CIOR 2017, held in Bandung, Indonesia. Highlighting novel technologies in the area of Improved Oil Recovery, it discusses a range of topics, including enhanced oil recovery, hydraulic fracturing, production optimization, petrophysics and formation evaluation.